2020
DOI: 10.1111/hae.14006
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasound for assessment of musculoskeletal disease in persons with haemophilia: Results of an International Prophylaxis Study Group global survey

Abstract: Aim: The objective of this survey was to understand the global trends of imaging assessments in persons with haemophilia, focusing on point-of-care ultrasound (POCUS). Insights into the barriers impeding its widespread proliferation as a frontline imaging modality were obtained. Methods: The survey opened in September of 2017 and closed in May of 2018. Haemophilia Treatment Centres (HTCs) treating both paediatric/adult patients were the population of interest. A REDCap survey of 25 questions was disseminated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 31 publications
1
37
1
Order By: Relevance
“…This was accomplished by joint examinations with point-of-care MSKUS/PD, increasingly evolving as a tool to detect hemarthrosis in hemophilia. 16,31,32 Although we found no convincing evidence that any of the 10 biomarkers characterized longitudinal joint health changes in our cohort, we did identify several markers that fluctuated in association Among the 10 joint-specific collagen turnover markers measured in our study, we found that a distinct set of biomarkers related to basement membrane and endothelial cell turnover increased specifically during acute hemarthrosis, and distinguished hemarthrosis from other painful episodes. Both type IV collagen synthesis and degradation markers were found to be elevated in association with joint bleeding and not during nonbleeding painful episodes, adding to the mounting evidence that hemarthrosis and synovial vascular remodeling are linked.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…This was accomplished by joint examinations with point-of-care MSKUS/PD, increasingly evolving as a tool to detect hemarthrosis in hemophilia. 16,31,32 Although we found no convincing evidence that any of the 10 biomarkers characterized longitudinal joint health changes in our cohort, we did identify several markers that fluctuated in association Among the 10 joint-specific collagen turnover markers measured in our study, we found that a distinct set of biomarkers related to basement membrane and endothelial cell turnover increased specifically during acute hemarthrosis, and distinguished hemarthrosis from other painful episodes. Both type IV collagen synthesis and degradation markers were found to be elevated in association with joint bleeding and not during nonbleeding painful episodes, adding to the mounting evidence that hemarthrosis and synovial vascular remodeling are linked.…”
Section: Discussioncontrasting
confidence: 59%
“…To examine the utility of biomarkers for assessing joint health in the context of arthropathy and fluctuating joint pains, it was critical to objectively establish the presence of hemarthrosis. This was accomplished by joint examinations with point‐of‐care MSKUS/PD, increasingly evolving as a tool to detect hemarthrosis in hemophilia 16,31,32 …”
Section: Discussionmentioning
confidence: 99%
“…Point-of-care ultrasound can be considered for early detection of synovial changes, cartilage lesions and diagnosis of acute bleeding [6], although survey findings suggest that it is used routinely in only 60%, 43%, and 47% of haemophilia treatment centres in Europe, North America, and the rest of the world, respectively [40]. In addition, only a quarter of physiotherapists report being able to independently use the technology [36].…”
Section: Monitoring Joint Health and Physical Functioningmentioning
confidence: 99%
“…A France group demonstrated that the finger pulp had the highest radiation exposure, especially at the left thumb and forefinger. The radiation effects can be avoided by fixing the injection needle [18].…”
Section: Patient Conditionmentioning
confidence: 99%